Science Teachers’ Perceptions of Integrating Cirebon Culture into Science Education: A Case Study - Putri Sekar Melati; Lilit Rusyati; Taufik Rahman (Scientiae Educatia: Jurnal Pendidikan Sains, 2025)
The Cirebon culture, a fusion of Sundanese, Javanese, and Islamic components, can be integrated into the science education curriculum. Nonetheless, research on how science teachers understand and utilize cultural integration in their teaching appears to be lacking. This research describes science teachers' understanding of integrating local culture into science education, the problems they face, and the possibilities these perspectives offer for the teaching and learning process. A case study was used, including interviews with science teachers and experts in Cirebon culture. NVivo software was used to analyze the data by coding responses concerning the role of Cirebon culture in science education. Findings from this study show that science teachers appreciate integrating culture into teaching, particularly the use of traditional, folklore, and environmental wisdom as contexts for teaching science concepts. Despite the glaring opportunities, challenges such as modernization, resource limitation, and institutional barriers negatively impact implementation. However, there is an opportunity to develop culture-based science education that responds to the local community, digital technology, and multidisciplinary approaches. This study demonstrates the need for curriculum change, emphasizing the integration of local cultural context without neglecting scientific standards. Integrating Cirebon cultural values allows students to simultaneously appreciate, comprehend, and integrate culture and environmental awareness with Science.